The Invasion of Sennacherib in the Book of Kings: A Source-Critical and Rhetorical Study of 2 Kings 18–19. By Paul S. Evans - Clements, Ronald Ernest (The journal of theological studies, 2011)
Since the publication in 1851 of news of the discovery of the Sennacherib Chronicle the biblical account of the threat to Jerusalem posed by the forces of Assyria in 701 bce has posed a challenge to biblical historians. Recent years have witnessed a near-tidal wave of fresh attempts to explain the reports of an intervention by the ‘Angel of Yahweh’ to slaughter in a single night 185,000 of the attacking force, and thereby to save the city and its king (2 Kgs. 18:35). Evans's reopening of current issues in the study begins with a full and detailed examination of the analysis initiated by Bernhardt Stade of the account recorded in 2 Kings 18–19, which he labels the Stade–Childs position. B. S.